Reconstruction of Mineral and Coal Mining Law Enforcement for The People's Welfare - Prisna Setyowati; Bambang Soesatyo (CV. Green Publisher Indonesia, 2026)
As mandated by Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia, this study aims to examine and reconstruct Indonesia’s mineral and coal mining (minerba) law enforcement, which has not yet fully realized public welfare. This study employed a normative legal research method using statutory and conceptual approaches. The findings show that, despite the provisions contained in Law Number 3 of 2020 concerning Mineral and Coal Mining and Law Number 32 of 2009 concerning Environmental Protection and Management, several significant legal gaps remain, including the lack of integration of strict liability, weak administrative sanctions, the absence of an effective mechanism for restoring community rights, and fragmented supervisory institutions. These gaps have contributed to an imbalance between natural resource exploitation and community welfare, as well as increased environmental degradation. Therefore, a comprehensive reconstruction of law enforcement is needed through the strengthening of administrative sanctions, the integration of the principle of strict liability into the minerba regime, the establishment of a community compensation mechanism, and the reinforcement of integrated cross-sectoral supervision. Furthermore, law enforcement approaches should be directed toward restorative justice and ecological justice, emphasizing environmental restoration and community well-being. Thus, mineral and coal mining law enforcement is expected to serve as an instrument of social justice and environmental sustainability in achieving public prosperity.